2022
DOI: 10.4082/kjfm.21.0223
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Associating Therapeutic Patient Education with Rehabilitation in the Management of Chronic Low Back Pain: A Randomized Controlled Trial

Abstract: Background: This study aimed to assess the benefits of associating rehabilitation with therapeutic patient education (TPE) to decrease fear-avoidance belief and pain and improve function in adults with chronic low back pain (CLBP).Methods: This randomized controlled study included 100 patients with CLBP according to the CONSORT (Consolidated Standards of Reporting Trials) guidelines. The patients were divided into two teams: group A that participated in the TPE in association with rehabilitation and group B th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Among the included RCTs, 10 (15.2%) studies 42 , 43 , 47 , 49 , 54 , 57 , 67 , 81 , 88 , 98 had a low overall risk of bias, 37 (56.1%) 33 , 35 , 36 , 38 40 , 44 , 45 , 48 , 50 52 , 59 61 , 63 66 , 68 71 , 73 , 75 – 78 , 84 – 87 , 91 94 , 97 exhibited some concerns, and 19 (28.7%) 34 , 37 , 41 , 46 , 53 , 55 , 56 , 58 , 62 , 72 , 74 , 79 , 80 , 82 , 83 , 89 , 90 , 95 , 96 had a high overall risk of bias. The majority of RCTs presented low risks of missing outcome data (72.7%) and randomization (75.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included RCTs, 10 (15.2%) studies 42 , 43 , 47 , 49 , 54 , 57 , 67 , 81 , 88 , 98 had a low overall risk of bias, 37 (56.1%) 33 , 35 , 36 , 38 40 , 44 , 45 , 48 , 50 52 , 59 61 , 63 66 , 68 71 , 73 , 75 – 78 , 84 – 87 , 91 94 , 97 exhibited some concerns, and 19 (28.7%) 34 , 37 , 41 , 46 , 53 , 55 , 56 , 58 , 62 , 72 , 74 , 79 , 80 , 82 , 83 , 89 , 90 , 95 , 96 had a high overall risk of bias. The majority of RCTs presented low risks of missing outcome data (72.7%) and randomization (75.8%).…”
Section: Resultsmentioning
confidence: 99%
“…In the NMA involving 24 RCTs 34 38 , 43 , 45 , 49 , 51 , 52 , 54 , 59 , 68 70 , 72 , 75 79 , 84 , 88 , 97 , 1722 participants, and 7 categories of interventions with six loops (Fig. 4 ), mind body therapy (pooled SMD = −1.35, 95% CI: −1.90 to −0.80), multicomponent intervention (pooled SMD = −0.47, 95% CI: −0.88 to −0.06), and biopsychosocial approach (pooled SMD = −0.46, 95% CI: −0.79 to −0.14) were superior to the control group in managing anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated greater reductions in TSK scores compared with other interventions when exercise or graded exposure is combined with a cognitivebehavioral approach 47 or pain education intervention. 48 However, other studies evaluating education or exercise alone compared with a combined approach have found no differences in pain-related fear of movement. 49,50 In these studies, no specific efforts were made to consolidate links between PSE and the pain experience during exercise, potentially highlighting the need for reflective learning as a core component of an exposure therapy approach.…”
Section: Discussionmentioning
confidence: 97%
“…We sought to integrate education principles with VR gameplay by providing constructive reinforcement of helpful cognitions through reflective interviewing and highlighting positive movement through video feedback. Previous studies have demonstrated greater reductions in TSK scores compared with other interventions when exercise or graded exposure is combined with a cognitive-behavioral approach 47 or pain education intervention 48 . However, other studies evaluating education or exercise alone compared with a combined approach have found no differences in pain-related fear of movement 49,50 .…”
Section: Discussionmentioning
confidence: 99%